Electromagnetic Characteristics Measurement Setup at Variable Temperatures Using a Coaxial Cell - Thibaut Letertre; Philippe Pouliguen; Pierre Sabouroux (Advances in Materials Science and Engineering)
This article presents an easy way to measure frequency dependence of the complex permittivity and complex permeability for any kind of material from 10 MHz to 6 GHz, with temperature variation between the ambient temperature and 85°C. This work is based on a well-known transmission/reflection technique using a coaxial line equipped with a thermoregulation system to manage temperature variations in the sample confinement area. The paper underlines some effects which have to be taken into account with temperature variation. APU10 and cyclohexanol are presented as examples of solid and liquid reference materials.